Visualisasi Area Tanam Perkebunan Berbasis WebGIS Menggunakan Data Foto Udara Resolusi Tinggi - Ibrahim Rivalzi; Muhammad Ismail; Dedy Fitriawan; Eva Purnamasari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Spatial distribution and visualization of planting areas in PTPN IV Regional 4 Kayu Aro Unit were conducted using high-resolution aerial imagery and Geographic Information System (GIS). This study aims to identify the distribution of planting areas and develop a WebGIS as an interactive spatial visualization tool that can support the monitoring and management of plantation land. The methods used include visual interpretation of high-resolution aerial photos, land use digitization, GIS spatial analysis, and WebGIS implementation based on QGIS2Web. Land use classification distinguished planting and non-planting areas, supported by slope analysis to evaluate topographic influence on land utilization. Plantation areas are predominantly occupied by active planting zones, with the highest percentage recorded in Afdeling E (95.881%), followed by Afdeling G (92.735%), Afdeling F (92.689%), and Afdeling D (92.601%). Afdeling A shows the lowest planting proportion at 58.84%, indicating a relatively higher concentration of non-planting areas. Spatial patterns indicate that planting areas are generally distributed on flat to undulating slopes, representing more suitable conditions for cultivation and plantation management. Spatial data and attribute information were integrated into a WebGIS platform to support interactive visualization, spatial monitoring, and information accessibility. The research results show that Afdeling E has the highest planted area percentage at 95.88%, while Afdeling A has the lowest at 58.84%. Black Box testing shows that all WebGIS features work with a 100% success rate.